ЗАМОНАВИЙ ТИЛЛАРНИ ЎҚИТИШДА МЕТОДИК ТЕХНОЛОГИЯЛАРНИНГ ЎЗИГА ХОС ХУСУСИЯТЛАРИ («MODERN PHILOLOGICAL PARADIGMS: INTERACTION OF TRADITIONS AND INNOVATIONS», 2025)
As it turns out, foreign language teaching focuses on certain technical and pragmatic rules.The specific characteristics of pedagogical technologies relate to the use of such technologies. Conducting Pedagogic technology in the classroom in modern new ways is one of the requirements of today. Pedagogic technology mainly consists of a set of methods and techniques that help to clearly and effectively organize educational activities in the 30s of the 20th century.
Keywords: foreign language, pedagogical technology, method, pedagogical master, pedagogical technique, teaching methods.